Corruption and inequality: a model of multiple equilibria. - Pinzón, Kathia (2021)
This article presents a theoretical mathematical model that addresses the issue of corruption from an economic perspective, assuming that agents respond to economic incentives (more specifically, relative profitability), and that each one of them has a “degree of resistance to participate in acts of corruption ”(moral cost). Within this framework, the point that we explore in greater detail is the relationship between inequality and corruption. From the perspective of complexity, it makes no sense to ask which cause to which, but rather how equilibria appear, disappear, or shift in the face of a more equal or unequal distribution of the capital stock or moral cost, and which income distribution (originated at work, or in profitability of capital in licit or illicit activities) occurs as a result. These two issues, corruption and inequality, are becoming increasingly relevant, especially in underdeveloped countries (as is the case in Latin America), where both are dramatically present, even calling into question the legitimacy of political systems.